2011
DOI: 10.5005/jp-journals-10021-1020
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrics of Permanent Dentition in Chennai Population

Abstract: As compared to other ethnic groups relatively few measurements on tooth size have been made on Indian population. Hence, a study was carried out in Department of Orthodontics, Saveetha Dental College, Chennai, to discern the average clinical crown dimensions for cervicoincisal heights (CIH) and mesiodistal widths (MDW), permanent dentition for the local population, to find out the amount of variation in CIH and MDW between males and females, between right and left sides and tooth showing maximum and minimum va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The greater the CW/CL ratio, the squarer the teeth, and the smaller the CW/CL ratio, the narrower the teeth. Similar to our study, Sridhar et al's research on the Chennai population showed that the cervico-incisal height and mesiodistal width are generally larger for male teeth than for female teeth [12]. Singh and Goyal concluded that the mesiodistal crown dimensions of male teeth are larger than those of females [13].…”
Section: Discussionsupporting
confidence: 89%
“…The greater the CW/CL ratio, the squarer the teeth, and the smaller the CW/CL ratio, the narrower the teeth. Similar to our study, Sridhar et al's research on the Chennai population showed that the cervico-incisal height and mesiodistal width are generally larger for male teeth than for female teeth [12]. Singh and Goyal concluded that the mesiodistal crown dimensions of male teeth are larger than those of females [13].…”
Section: Discussionsupporting
confidence: 89%
“…Leach liquor from Printed Circuit Board scrap was prepared according to literature [14]. 10mL of leach solution was passed into a column (25 cm length, 1 cm id) containing 1 g of sodium form of resin.…”
Section: 4b Recovery Of Copper and Nickel From Printed Circuit Boarmentioning
confidence: 99%